A large diversity of organohalogen contaminants reach the meso- and bathypelagic organisms in the Bay of Biscay (northeast Atlantic). (November 2022) - Munschy, C.; Spitz, J.; Bely, N.; Héas-Moisan, K.; Olivier, N.; Pollono, C.; Chouvelon, T.
Abstract: Deep-sea ecosystems play a key role in the cycling and vertical transfer of matter and energy in oceans. Although the contamination of deep-sea demersal and benthic organisms by persistent organic pollutants has been proven, deep pelagic species have been far less studied. To fill these gaps, we studied the occurrence of a large variety of hydrophobic organic contaminants including polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), legacy and alternative brominated flame retardants (BFRs) and per - and polyfluoroalkyl substances (PFASs) in crustaceans and fish species collected in the Bay of Biscay, northeast Atlantic. The results highlighted the global predominance of PCBs in fish, followed by OCPs, PFASs and PBDEs, with highly variable concentrations among species. Most of the chlorinated or brominated contaminants showed increasing concentrations with increasing δ 15 N values, while most PFASs showed inverse trends. The contaminant profiles and diagnostic ratios revealed species-specific metabolic capacities and peculiar contribution of highly-brominated BFRs. Highlights: Organohalogen contaminants were ubiquitous in deep pelagic crustaceans and fish. PCBs were predominant in fish followed by OCPs, PFASs and PBDEs. BFR profiles were peculiar with high contributions of BDE-209 and DBDPE. Specific ratios highlight species-specific metabolic capacities. Long-chain PFCAs showed biodilution with increasing δ 15 N values.